1992
DOI: 10.2307/2159681
|View full text |Cite
|
Sign up to set email alerts
|

On Weak Containment Properties

Abstract: Abstract.We prove, that two concepts of weak containment do not coincide, contradicting results in [1, Lemma 3.3 and Proposition 3.4]. The statement of Theorem 3.5 remains valid. There exist infinite tall compact groups G (i.e. the set {a e G, dim er = n} is finite for each positive integer n ) having the mean-zero weak containment property. Such groups do not have the dual Bohr approximation property or AP(G) ^ Cg(G).Let G be a compact group, then G is said to have the mean-zero weak containment property if t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Then G is called a tall group . Some properties of tall groups, specially profinite tall groups, have been studied in . Example Let us use the notations and facts mentioned in the proof of Proposition .…”
Section: Amenability Of Hypergroup Algebrasmentioning
confidence: 99%
“…Then G is called a tall group . Some properties of tall groups, specially profinite tall groups, have been studied in . Example Let us use the notations and facts mentioned in the proof of Proposition .…”
Section: Amenability Of Hypergroup Algebrasmentioning
confidence: 99%
“…where CK L 1 (G) (L 1 (G), L ∞ (G)) are the completely compact convolution maps, and then argue via (3). The isomorphisms (3) and ( 4) complement the analysis of [12,22,57], where, contrary to the classical setting, it was shown that, in general, complete compactness was insufficient to recover the quantum Bohr compactification. Our results imply that for a large class of quantum groups one can recover the (discrete dual of the) quantum Bohr compactification by considering completely nuclear convolution maps, as opposed to completely compact ones.…”
Section: Introductionmentioning
confidence: 88%
“…That is, one cannot recover the quantum Bohr compactification by considering (completely) compact module maps L 1 (G) → L ∞ (G). Indeed, by [22, §4.1],[12, Proposition 3.1] and [57, Proposition 1], if G is any infinite tall compact group with the mean-zero weak containment property (see [12,57]) then the rank-one projection p ∈ V N (G) onto the constant functions in L 2 (G) defines a completely compact A(G)-module map, but…”
Section: Completely Nuclear Multipliers and The Quantum Bohr Compacti...mentioning
confidence: 99%
“…. This is [9,Theorem 3.5], but be aware of some errors in preliminary results; these errors are partly corrected in [40]; in particular [40, Proposition 1] shows the result we are interested in. Remarkably, in full generality, it is still unknown if AP ( Ĝ) is even a C * -algebra, never-mind whether it satisfies any obvious interpretation as a "compactification".…”
Section: There Exists a Compact Groupmentioning
confidence: 99%